PEMBUATAN LAPISAN TIPIS MANGAN OKSIDA DAN LITIUM-MANGAN OKSIDA PADA SUBSTRAT KACA DENGAN METODA DIP-COATING MELALUI PROSES SOL-GEL - Warda Ningsih, Sherly Kasuma (Sainstek, 2010)
Preparation of manganese oxide and lithium-manganese oxide thin layer on glass substrate by dip-coating method via sol-gel process have been investigated. Manganese (II) nitrate tetrahidrate and lithium chloride were used as precursors, isopropanol as solvent and DEA as additive. Dip-coating process have been done on glass substrate at 6 times with dipping time around 2 minutes for each layer process and dried at 110-120 oC around 15 minutes. Dried samples heated at 400 oC, 500oC and 600oC during 120 minutes. Black thin layer were obtained as products. The products were characterized by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The XRD pattern was shown manganese oxide thin layer were obtained Mn2O3 only. Crystal structure of Mn2O3 was orthorombic with crystallite size around 13.0 nm (JCPDS No. 24-0508). SEM image (at 500oC) showed uniform and smooth surfaces with grain size around 0,01 m. The XRD patterns showed that lithium-manganese oxide thin layer were obtained LiMn2O4 and small amount of Mn2O3. Crystal structure of LiMn2O4 was spinnel with crystallite size around 16.86 nm (JCPDS No. 35-0782). SEM images (at 400 and 500oC) showed fiber form were produced generally and spheric form at 600oC. Key words : lithium-manganese oxide, dip-coating, sol-gel, fiber, spheric,